ANALISIS USAHA BUDIDAYA PERIKANAN AIR TAWAR DI KABUPATEN KAMPAR PROVINSI RIAU - Limetry Liana (UIR Press, 2015)
Kampar is one of regencies in Riau Province which consistently develop fishery sector, especially freshwater fishery farming. Currently, there are two types of freshwater fishery cultures developed in Kampar Regency i.e., catfish in the pond and fat fish in cages. This study aattempted to analyze the freshwater fishery businesses in Kampar Regency, including cultivation techniques, costs, revenues, benefit and Break-even Point (BEP) of freshwater fishery businesses in Kampar Regency, especially pond and cages fish cultures. Data were collected with census method from 43 fishermen and then analyzed using quantitatively descriptive technique. The results showed that the largest cost in fish production was for feed, contributing about 77.72% and 46.46% of the total costs for pond and cage fish cultures, respectively. Furthermore, the average production cost incurred for each business accounting for Rp 43,273,744.44 and Rp 33,046,937.65 with production is 4,320 kg and 1,750 kg, respectively. The average income received was Rp 47,515,000.00 for pond fishery businesses and Rp 36,755,000.00 for cage fishery businesses, while the level profit was Rp 4,241,255.56 and Rp 3,708,062.35 with an efficiency rate of 1.09 and 1.11, respectively.